Effects of mobile-assisted reading materials on children’s L1 lexical development - Liu, Xueli; Ni, Chuanbin; Liu, Yan (Frontiers in Psychology, 2023)
Despite the wide and extensive use of mobile-assisted devices, the effectiveness of children’s L1 learning with these mobile-assisted technologies has been less discussed. This study aims to explore the effects of mobile-assisted reading materials on Chinese children’s L1 vocabulary learning. We adopted a longitudinal and quasi-experimental design consisting of an experiment group using the mobile-assisted materials and a control group using the traditional paper materials, and took children’s lexical development as indexed by assessing the parameter, lexical diversity, in different testing times. The results showed that (1) children’s L1 vocabulary learning effectiveness of using mobile-assisted materials is as similar as that of using conventional paper materials in general, and (2) the changing patterns of children’s L1 lexical development using mobile-assisted materials in different testing times are various. Specifically speaking, (a) in the posttest 1 (the first month), compared with the traditional paper reading materials, the mobile-assisted reading materials have a facilitating effect on the primary school students’ L1 vocabulary learning; (b) in the posttest 2 (the second month), children’s vocabulary learning effectiveness is inhibited by the mobile-assisted reading materials; (c) in the delayed posttest (the fourth month), there is no difference in the learning effectiveness by these two different kinds of learning materials and the lexical diversity increases slowly but steadily. We analyzed the results from research-design factors and learner-related factors, hoping to shed light on children’s mobile-assisted language learning research.